Football-related maxillofacial injuries. Issue 5 (June 2022) - Gallagher, N.; Collyer, J.; Shelley, M.J.; Sneddon, K.J.; Bowe, C.M.
Abstract: Maxillofacial injuries sustained playing sports are becoming increasingly common, and in the UK where football is the most popular team sport, associated maxillofacial injuries are a regular occurrence. This study retrospectively examined data on patients who were referred with facial injuries sustained playing football between 2007 and 2019 (n = 265). Demographics, mechanism of injury, diagnosis, and treatment received were analysed. The mean (SD) age was 25 (11.0) years (range 3-85) and there was a strong male predominance (n = 256, 97% male). Facial fractures were diagnosed in 143 (54%) patients. The most common injury was a midface fracture and the most common mechanism of injury was a clash of heads. Patients with a facial fracture were significantly more likely to have sustained a concurrent head injury (p  =  0.006). Those who were elbowed or punched were significantly more likely to have a facial fracture than a soft tissue or dentoalveolar injury (p ≤ 0.05). Players who clashed heads were significantly more likely to have a midface fracture (p ≤ 0.001). In conclusion, football- related maxillofacial injuries predominantly affect young adult males following a clash of heads. An elbow or punch to the face carries a significant risk of facial fracture and concurrent head injury. Therefore, to reduce the percentage of maxillofacial injuries seen in this sport, observed intentional contact between players, using an elbow or fist to the face in particular, must continue to carry the highest sanction.